Feasibility and Safeguards Policy for Nuclear Power Plants: A Case Study in Indonesia within the NPT Framework, Emphasizing Global Security Analysis - Karolus Evantino; Agus Winarna; Gregorius Henu Basworo; Habibie Satrio Nugroho (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study examines the feasibility of a United Nations (UN) peacekeeping force with nuclear capabilities to improve global security. It starts with a historical overview of nuclear weapons and international agreements. The research then addresses challenges such as proliferation, cyber threats, and nuclear energy expansion. This paper analyses Indonesia's stance on the Iranian nuclear issue and the challenges of balancing international relations with domestic pressures, with a focus on its role in the UN Security Council. Using a descriptive qualitative approach, the research assesses global security, technical challenges, political considerations, moral implications, cost allocation, roles of non-nuclear states, regional impacts, transparency, nuclear disarmament, public perception, and alternative security approaches. The study highlights the importance of a comprehensive evaluation that takes into account technical, political, ethical, economic, and regional dimensions. The text emphasizes the importance of transparency, accountability, and international consensus in achieving effective global security. While acknowledging both the potential benefits and risks, the research recommends careful consideration and multilateral diplomatic efforts to promote global stability.